Hungary : Report on the Observance of Standards and Codes-Fiscal Transparency Module-Update. (IMF Staff Country Reports; Country Report ;, 2004)
This paper presents an update to the Report on the Observance of Standards and Codes (ROSC) on Fiscal Transparency for Hungary. The paper discusses that from 2004, and in the context of the 2004 budget law, the use of privatization receipts has been limited to financing infrastructure development projects included in the central budget and approved by Parliament. Hungary's 2003 Pre-Accession Economic Program submitted to the European Commission improved its analysis of medium-term fiscal risks and provided an estimate of the structural fiscal deficit.